Inhibition of eIF5A hypusination pathway as a new pharmacological target for stroke therapy. Issue 5 (May 2021) - Bourourou, Miled; Gouix, Elsa; Melis, Nicolas; Friard, Jonas; Heurteaux, Catherine; Tauc, Michel; Blondeau, Nicolas
In eukaryotes, the polyamine pathway generates spermidine that activates the hypusination of the translation factor eukaryotic initiation factor 5A (eIF5A). Hypusinated-eIF5A modulates translation, elongation, termination and mitochondrial function. Evidence in model organisms like drosophila suggests that targeting polyamines synthesis might be of interest against ischemia. However, the potential of targeting eIF5A hypusination in stroke, the major therapeutic challenge specific to ischemia, is currently unknown. Using in vitro models of ischemic-related stress, we documented that GC7, a specific inhibitor of a key enzyme in the eIF5A activation pathway, affords neuronal protection. We identified the preservation of mitochondrial function and thereby the prevention of toxic ROS generation as major processes of GC7 protection. To represent a thoughtful opportunity of clinical translation, we explored whether GC7 administration reduces the infarct volume and functional deficits in an in vivo transient focal cerebral ischemia (tFCI) model in mice. A single GC7 pre- or post-treatment significantly reduces the infarct volume post-stroke. Moreover, GC7-post-treatment significantly improves mouse performance in the rotarod and Morris water-maze, highlighting beneficial effects on motor and cognitive post-stroke deficits. Our results identify the targeting of the polyamine-eIF5A-hypusine axis as a new therapeutic opportunity and new paradigm of research in stroke and ischemic diseases.